Phylogenetic analysis and protective effects of thymol and its chromatographic fractions from a novel wild mushroom in combating oxidative stress - M. Subbulakshmi; Sugapriya Dhanasekaran; S. Abirami; M. Kannan; R. Palaniappan; Divya Venugopal (Food Science and Human Wellness)
Mushrooms are good sources of phytochemicals that have antioxidant and anti-proliferative effects. This study identified a unique isoform of 18S rRNA gene (864 bp) from a novel wild mushroom (SMK-1) (GenBank accession number: SUB3267363). Thin layer chromatographic (TLC) profiling of the methanolic extract of the dried mushroom fruiting bodies of SMK-1 revealed the presence of phenolic and flavonoid fractions with retention factor (Rf) values of 0.955 and 0.927 respectively. The GC/MS chromatograms of the SMK-1 methanolic extract identified the main bioactive compound was phenol, 5-methyl-2-(1-methylethyl) (74.00%) (thymol). The radical scavenging activity for the flavonoid fraction was greater than the phenolic fractions (Rf–phenolics fractions > Rf–flavonoid fractions) with the antioxidant activity more than that of standard ascorbic acid. Also, the phenolic and flavonoid fractions of SMK-1 expressed cytotoxic effects in HeLa cells with IC50 values ranging from 5 μg/mL to 80 μg/mL in a dose-dependent manner. This present research highlights the presence of high thymol concentration in a novel wild mushroom that has antioxidant and anti-poliferative potential with therapeutic benefits. The application of thymol natural products from novel mushroom SMK-1 as nutrition supplements could inhibit oxidative stress triggered by numerous pathologies that may pave the way to develop a new therapeutic natural drug.